CCN production by new particle formation in the free troposphere - C. Rose; K. Sellegri; I. Moreno; F. Velarde; M. Ramonet; K. Weinhold; R. Krejci; M. Andrade; A. Wiedensohler; P. Ginot; P. Laj (Atmospheric Chemistry and Physics, 2017)
Global models predict that new particle formation (NPF) is, in some environments, responsible for a substantial fraction of the total atmospheric particle number concentration and subsequently contributes significantly to cloud condensation nuclei (CCN) concentrations. NPF events were frequently observed at the highest atmospheric observatory in the world, on Chacaltaya (5240 m a.s.l.), Bolivia. The present study focuses on the impact of NPF on CCN population. Neutral cluster and Air Ion Spectrometer and mobility particle size spectrometer measurements were simultaneously used to follow the growth of particles from cluster sizes down to ∼ 2 nm up to CCN threshold sizes set to 50, 80 and 100 nm. Using measurements performed between 1 January and 31 December 2012, we found that 61 % of the 94 analysed events showed a clear particle growth and significant enhancement of the CCN-relevant particle number concentration. We evaluated the contribution of NPF, relative to the transport and growth of pre-existing particles, to CCN size. The averaged production of 50 nm particles during those events was 5072, and 1481 cm−3 for 100 nm particles, with a larger contribution of NPF compared to transport, especially during the wet season. The data set was further segregated into boundary layer (BL) and free troposphere (FT) conditions at the site. The NPF frequency of occurrence was higher in the BL (48 %) compared to the FT (39 %). Particle condensational growth was more frequently observed for events initiated in the FT, but on average faster for those initiated in the BL, when the amount of condensable species was most probably larger. As a result, the potential to form new CCN was higher for events initiated in the BL (67 % against 53 % in the FT). In contrast, higher CCN number concentration increases were found when the NPF process initially occurred in the FT, under less polluted conditions. This work highlights the competition between particle growth and the removal of freshly nucleated particles by coagulation processes. The results support model predictions which suggest that NPF is an effective source of CCN in some environments, and thus may influence regional climate through cloud-related radiative processes.